Track of K.H Muhammad Nur's Da'wah Strategy in the Development of Islam on Sarappo Lompo Island - Nurhaolillah Nurhaolillah (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study traces the footsteps of K.H Muhammad Nur in the development of Islam on the island of Sarappo Lompo. This study attempts to answer two questions, namely K.H Muhammad Nur's da'wah strategy in the development of Islam on the island of Sarappo Lompo and the influence of K.H Muhammad Nur's da'wah strategy in the development of Islam on the island of Sarappo Lompo. This research is descriptive qualitative research, using historical, anthropological, sociological and religious approaches. This approach is supported by heuristic stages, source verification, interpretation and historiography writing with data obtained from oral sources (interviews), family documentation and socio-religious observations. The results of the study show that his da'wah strategy combines gradual guidance (tarqiyah) with a cultural approach that adapts Islamic teachings (cultural). This approach is effective in the process of guidance and education, strengthening solidarity, and improving morality. Its influence is evident through changes in the diversity patterns of the community from traditional practices with minimal religious understanding to more structured religious activities. Through Qur'anic teaching and regular religious study sessions, the community experienced an increase in Islamic literacy, strengthened solidarity, and improved morality through the revitalisation of religious traditions that are more in line with Islamic values.